Constraining an Irregular Peptide Secondary Structure through Ring‐Closing Alkyne Metathesis. (6th September 2016) - Cromm, Philipp M.; Wallraven, Kerstin; Glas, Adrian; Bier, David; Fürstner, Alois; Ottmann, Christian; Grossmann, Tom N.
Abstract: Macrocyclization can be used to constrain peptides in their bioactive conformations, thereby supporting target affinity and bioactivity. In particular, for the targeting of challenging protein–protein interactions, macrocyclic peptides have proven to be very useful. Available approaches focus on the stabilization of α‐helices, which limits their general applicability. Here we report for the first time on the use of ring‐closing alkyne metathesis for the stabilization of an irregular peptide secondary structure. A small library of alkyne‐crosslinked peptides provided a number of derivatives with improved target affinity relative to the linear parent peptide. In addition, we report the crystal structure of the highest‐affinity derivative in a complex with its protein target 14‐3‐3ζ. It can be expected that the alkyne‐based macrocyclization of irregular binding epitopes should give rise to new scaffolds suitable for targeting of currently intractable proteins. Abstract : Rigidification of macrocycles : We report alkyne‐macrocyclized peptidomimetics that are accessible through ring‐closing alkyne metathesis. The resulting molecules target the human adaptor protein 14‐3‐3 through direct engagement of the alkyne crosslink. The crystal structure of the highest‐affinity derivative in a complex with 14‐3‐3 was determined.